Kāns̄ưpkhon phūmpanyā th̨ōngthin Čhangwat N̨ōng Khāi ph̄ưa pen l̄æng rīanrū nai kānbūranā kānrīan kāns̨ōn - Somkhit Chaiyawong (Sūn Kh̨ōmūn Sangkhom Watthanatham Th̨ōngthin Čhangwat N̨ōng Khāi Khēt Kānsưksā 9, 2002)
Study of products and culture from the local wisdom of the people in Nong Khai Province, Northeastern Thailand.